Older age and sex differences in the proportion of vital signs flagged as abnormal - Jean-Philippe Emond; Vincent Weng-Jy Cheung; Ariel Mundo Ortiz; Robert Goulden; Sahar Saeed; Philippe Desmarais; Michaël Chassé; Christina Wolfson; Quoc Dinh Nguyen (PLoS ONE, 2026)
Background The variability of vital signs thresholds has not been well described in relation to older age and sex assigned at birth. Significant variations may influence clinical interpretation of vital signs, most notably the thresholds at which investigations or treatments are initiated. Our objective was to compare, in stable health status, the percentage of abnormal values (flagging percentage) of standard vital signs thresholds of adults aged 45 years and older and to determine centile-based thresholds by age and sex. Methods A retrospective observational study was conducted using data from the Centre for the Integration and Analysis of Medical Data (CITADEL) at the Centre hospitalier de l’Université de Montréal (CHUM), a tertiary care hospital. All inpatients and outpatients, from January 2012 to December 2021, were included. For individuals with multiple visits, a single hospitalization or a single outpatient visit was selected at random for inclusion. To reflect a stable health status, the last vital signs recorded before hospital discharge were selected and in-hospital deaths were excluded. Flagging percentages were identified using a quantile-based approach. Age and sex specific centile-based thresholds were determined by identifying values at the 2.5 th and 97.5 th centiles. Flagging percentages and centile values for systolic and diastolic blood pressure, heart rate, and temperature were analyzed by age group (45–54, 55–64, 65–74, 75–84, and 85 + years) and sex. Results The sample comprised 123,420 individuals, including 90,813 inpatients. Flagging percentages for the standard threshold of upper systolic blood pressure (140 mmHg) ranged from 13.3 (12.7–13.9) % (45-54y assigned female at birth (AFAB)) to 39.8 (38.6–41.0) % (85y+ AFAB). Flagging percentages for standard thresholds ranged between 0.1 (0.1–0.2) to 1.2 (1.0–1.4) % for upper temperature (37.8°C), lower temperature (35.0°C), and lower systolic blood pressure (90 mmHg). Across subgroups, the 97.5 th centile-based adapted thresholds varied between 158 (156−159) – 178 (177−180) mmHg for upper systolic blood pressure and between 37.2 (37.1–37.2) – 37.3 (37.3–37.3) °C for upper temperature. Conclusions Important differences in vital signs flagging percentages may affect their comparability by vital sign, age, and sex. Standard thresholds may need to be reassessed using clinical outcomes to factor age and sex differences.